DAMPAK PERTUMBUHAN PENDUDUK TERHADAP BEBAN SUMBER PENCEMAR DI DANAU SENTANI DENGAN MODEL SISTEM DINAMIK BERWAWASAN LINGKUNGAN - Auldry F. Walukow (Purifikasi, 2011)
This research was aimed to analyze the erosion in the watershed (watershed) Sentani and to apply dynamic system model to analyze the effect of population growth on the source of pollutant loads in Sentani Lake. Universal Soil Loss Equation (USLE) method was used to estimate soil erosion from land and dynamic system model using powersim 2.5D tools in order to obtain a model of sustainable Sentani Lake management. Results of this experiment showed that the dynamic model approach to the management and planning of settlements and agricultural areas around Sentani Lake might facilitate the solution of pollutant source, erosion, and deforestation problems and determination of strategic policy for coping with these problems In addition, population growth was a leverage factor to the increase of pollutant sources, the limitation of forest land, residential land erosion, and erosion of agricultural land. However, structural intervention to human settlements and agricultural land should also be performed. The dynamic model of pollutant sources was Archetype Shifting the Burden.